STYLE AND REGISTER - Siti Aisyah; Serli Talo Goro; Krisensia Prilly Odessya; Moh Rifki Habibi (INJOSEDU: International Journal of Social and Education, 2025)
This article discusses the concepts of style and register in the realm of sociolinguistics, which is a branch of linguistics that studies the relationship between language and society. Style refers to variations in language use based on situational context, level of formality, and social relationships between speakers, as discussed by Labov (1972) in his research on sociolinguistic patterns. Meanwhile, register refers to language variations that are influenced by certain fields of activity or professions, as described by Halliday (1978) in his theory of systemic functional linguistics. This article also explores factors that influence the choice of style and register, such as age, gender, social status, and communication goals, based on research contributions from Trudgill (1983) and Fishman (1968). By understanding style and register, deep insight can be gained into how language is used to reflect identity, build social relationships, and adapt communication in various contexts. This study not only strengthens previous sociolinguistic theories but also provides practical insights to support social interaction, language teaching, and the development of cross-cultural communication.